Asymptomatic Pulmonary Artery Intimal Sarcoma with Chest Wall Metastasis as an Initial Manifestation: An Autopsy Case - Tomoo Kakimoto; Mamoru Sasaki; Shojiroh Morinaga; Robert Nakayama; Naoto Minematsu (Case Reports in Medicine)
Pulmonary artery intimal sarcoma (PAIS) is a rare mesenchymal malignancy arising in the pulmonary trunk or proximal pulmonary artery and shows intraluminal growth. Clinical manifestations in PAIS are predominantly related to the pulmonary artery embolism, so cases with initial symptoms related to an extrapulmonary metastasis are unusual. The present report describes an 82-year-old man without any cardiopulmonary symptoms who was detected with an abnormal shadow on chest radiography during a routine health checkup. Contrast medium-enhanced chest computed tomography revealed an enhancing mass in the right pulmonary artery, pulmonary nodules, and a chest wall tumor corresponding to the abnormal shadow observed using chest radiography. A core needle biopsy for the chest wall tumor determined a pathological diagnosis of unclassified sarcoma. The patient was diagnosed with PAIS on the basis of clinical, radiological, and pathological correlations. He was scheduled to receive supportive care, but died of respiratory failure 1 year from the first visit. An autopsy revealed the pleomorphic sarcoma occupying the entire lumen of the right pulmonary artery with the only site of extrapulmonary metastasis in the chest wall. We should be aware of rare cases of asymptomatic PAIS found through routine health checkups.